Effect Of Internal Market Orientation On Organizational Commitment: Applied Study At Algerian Hotels - Agti, Djouhara; Louafi, Khaled (University of Eloued جامعة الوادي, 2019)
This paper aims to examine the level of internal market orientation IMO as seen from the perspective Algerian hotels’ employees, and its effect on their organizational commitment. The study is based on primary research conducted with data gathered from 341 employees of Algerian Hotels. The results indicate that all the three components of market orientation mentioned above determine the IMO level. Furthermore, the continuous emphasis on IMO by internal suppliers results in organizational commitment especially the third components’ response. The Study recommendations are also purposed.
مجلة رؤى المجلد التاسع العدد الأول
Keywords: Internal market; commitment; Algerian Hotels. Jel Classification Codes : M1 ; M12